Nutritional status of school age children in Abakaliki metropolis, Ebonyi State, Nigeria - Adanna Anthonia Umeokonkwo; Maryann Ugochi Ibekwe; Chukwuma David Umeokonkwo; Clifford Onuorah Okike; Obumneme Benaiah Ezeanosike; Bede Chidozie Ibe (BMC, 2020)
Abstract Background Malnutrition is a major public health problem with short and long-term adverse effects on children particularly in middle and low-income countries. Three out of every ten under-five children are said to be stunted and 19.4% underweight in Nigeria. In Ebonyi State, between 2013 and 2015, the proportion of preschool children with chronic undernutrition rose from 16.2 to 20.6%. Little is documented about the nutritional status of school-age children in Ebonyi State and Nigeria. Methods We conducted a descriptive cross-sectional study among 780 children aged 6 to 12 years from 10 primary schools in Abakaliki metropolis. A multistage sampling method was used to select the participants. A pre-tested interviewer-administered structured questionnaire was used to collect information from the children and their parents. Body Mass Index (BMI), Z scores of the weight for age, BMI for age and height for age were obtained using the WHO AnthroPlus software. We estimated the prevalence of undernutrition, over-nutrition, underweight, thinness, stunting, overweight and obesity. Result Out of 751 pupils that participated, 397 (52.9%) were females and 595 (79.2%) were in public schools. The overall prevalence of undernutrition was 15.7% and that of over-nutrition was 2.1%. The prevalence of underweight, thinness and stunting, overweight and obesity were 8, 7.2, 9.9, 1.4 and 0.7% respectively. The proportion of pupils who were thin was higher among males (8.7%), those attending public schools (8.6%) and those dwelling in rural parts of the metropolis (14.3%) compared to females (5.8%) private school attendees (1.9%) and urban dwellers (4.6%). Stunting was found to be higher among pupils attending public schools (11.8%) compared to those attending private schools (2.5%). The prevalence of stunting was 19.3% among the pupils residing in rural areas and 5% among the pupils living in urban areas of the metropolis. No pupil in private schools was underweight. Over-nutrition was not found among the pupils in rural areas. Conclusion Both under and over nutrition exist in Abakaliki metropolis. Undernutrition is the more prevalent form of malnutrition among school age children in the metropolis.